Normal Embryos from Mating Albino Male Mice with Hyperprolactinemia and Treated with Peganum Harmala Seed Extract - Hanoon, Hind A.; ALsadoon, Asawer K.; Naheema, Ghufran L. (American Journal of Biology and Natural Sciences, 2025)
The Zygophylaceae family includes Peganum harmala (P. harmala). Its medicinal effects make it important in traditional medicine. This research examined how aqueous extracts from Peganum harmala L. seeds affected male reproductive capability in white mice using olanzapine. The research examined how this therapy affected male mating, fertilization, and pregnancy. The average weight of 90 male mice aged 20–25 days was 25 g. The male mice were divided into three groups. The negative control group of 30 male patients got distilled water injections for 15 days. The positive control group of 30 male Olanzapin users received the medicine for the same time. Finally, 30 male subjects got Olanzapine for 15 days and 15 mg/kg Peganum harmala L. Seed aqueous extracts for 7 days in the third cohort. All experimental groups received six female volunteers before collecting male specimens. The research found that the second group, who underwent medication therapy alone, could not marry or fertilize after 21 days. This was caused by increased prolactin and low testosterone, which altered sperm properties. However, the third group, which got both the medication and the aqueous extract, had successful pregnancies and births. However, each female in this group had six children, and only two got pregnant. Healthy newborns without outward malformations are notable. This research found that Peganum harmala aqueous extracts significantly affect sperm defects and male hormone levels. Testosterone hormone concentration increased significantly (p<0.01), whereas prolactin hormone levels decreased significantly (p<0.01).